Resilience of social transfer programs to large unexpected shocks - Chowdhury, Shyamal; Bin Khaled, Muhammad Nahian; Mallick, Debdulal; Raghunathan, Kalyani; Rashid, Shahidur (Informa UK Limited, 2024)
Large, unexpected shocks are becoming more frequent, making the design of robust social transfer programs more vital than ever. We evaluate the performance of the Food Friendly Program (FFP), the largest in-kind social transfer program in Bangladesh, before and during the nation-wide COVID-19 lockdown. Using two-rounds of nationally representative household surveys combined with administrative data, we document that high leakages and large welfare losses are related to corruption. This contrasts with the performance of the pre-lockdown FFP, when leakage was low and coverage high. We then compare the performance of the FFP with two initiatives launched following the pandemic: an in-kind and cash transfer program, respectively. These programs have markedly higher levels of leakage than the FFP. Our findings are relevant to other large shocks, such as those caused by climate change, and have important policy implications for the design and delivery of transfer programs in developing countries characterized by institutional weaknesses.